Adipose-Derived Stem Cells for Cartilage Tissue Engineering: A Bibliometric Analysis of Trends and Themes - Zhang J; Wu K; Zhou L; Zheng S (Journal of Multidisciplinary Healthcare)
Jing Zhang,1,* Kai Wu,2,* Lin Zhou,3 Shusen Zheng3 1Department of Plastic and Aesthetic Center, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, People’s Republic of China; 2Spine Lab, Department of Orthopedic Surgery, The First Affiliated Hospital of Zhejiang University, Hangzhou, 310003, People’s Republic of China; 3Department of Hepatobiliary and Pancreatic Surgery, First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, China*These authors contributed equally to this workCorrespondence: Shusen Zheng, Email shusenzheng@zju.edu.cnPurpose: Adipose-derived stem cells (ADSCs) have shown great potential in cartilage tissue engineering (TE) due to their accessibility, high proliferation rate, and chondrogenic differentiation capacity. This study aims to systematically evaluate research trends, collaboration patterns, and emerging themes in ADSC-based cartilage TE through a bibliometric analysis, providing actionable insights to address knowledge gaps and advance the field.Patients and Methods: A systematic search was conducted on the Web of Science Core Collection (WoSCC) database to identify publications related to ADSCs and cartilage TE. Bibliometric and visualized analysis was performed using VOSviewers (V 1.6.20), CiteSpace (V 6.3.R1) and Bibliometrix (R 4.3.3).Results: A total of 436 English articles were analyzed, involving 2356 authors from 1532 institutions across 50 countries/regions, contributing to 189 journals. The annual growth rate of publications was 8.73%, peaking in 2021. China contributed the most articles (n=127, 29.1%), followed by the USA (n=65, 14.9%). Leading institutions included Kaohsiung Medical University and Duke University. Tissue Engineering Part A had the highest H-index (21) and the most publications (n = 26). Reis Rui L. and Gomes Manuela E. were among the most influential contributors. Keyword analysis revealed an early focus on “in-vitro” studies and “bone-marrow”, which later transitioned to “chondrogenic differentiation”, “growth”, and “regeneration”. Recent trends since 2020 include “ 3D printing”, “mesenchymal stem cells”, and “cartilage repair”, reflecting the field’s evolution towards advanced technologies and translational applications.Conclusion: This bibliometric analysis provides valuable guidance for researchers, clinicians, and policymakers, emphasizing the necessity of addressing translational challenges and fostering global collaboration to develop clinically effective solutions for cartilage repair and regeneration.Keywords: bibliometrics, research trends, cartilage repair, tissue engineering, adipose-derived stem cells, citespace, VOSviewer